2015
DOI: 10.1111/birt.12212
|View full text |Cite
|
Sign up to set email alerts
|

Choosing a Model of Maternity Care: Decision Support Needs of Australian Women

Abstract: This study demonstrates Australian women's unmet needs for information that supports them to effectively compare available options for model of maternity care. Findings provide clear direction on what information should be prioritized and ideal channels for information access to support quality decision-making in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…The most commonly reported reasons for choosing the OFW model of care were the lower financial cost and recommendations from care providers. This finding is consistent with a previously reported Australian study that found the cost was the most important factor, and care provider information was the most influential in choosing a maternity care model ( 24 ). Although the model of care, convenience, and availability of multiple services at one location was valued by women that attended OFW for their maternity care, it is not surprising that these factors were not frequently cited as reasons for choosing OFW as the service had been in operation for <12 months and was not widely known at the time of commencement of this study.…”
Section: Discussionsupporting
confidence: 92%
“…The most commonly reported reasons for choosing the OFW model of care were the lower financial cost and recommendations from care providers. This finding is consistent with a previously reported Australian study that found the cost was the most important factor, and care provider information was the most influential in choosing a maternity care model ( 24 ). Although the model of care, convenience, and availability of multiple services at one location was valued by women that attended OFW for their maternity care, it is not surprising that these factors were not frequently cited as reasons for choosing OFW as the service had been in operation for <12 months and was not widely known at the time of commencement of this study.…”
Section: Discussionsupporting
confidence: 92%
“…The results coincide with those mentioned by Stevens et al [43], McKinnon et al [44] or Downer [45] in relation to coping with childbirth, the possibilities of mobility, use of medical procedures or place of delivery. In this study, women have expressed a general need for information and support in decision-making regarding pregnancy or breastfeeding, which will allow them to play a more active role in the process.…”
Section: Discussionsupporting
confidence: 91%
“…Policymakers need to also be aware that changes in the quality gap for obstetrics care between public/private hospitals are likely to influence demand for PHI. Self‐reports suggest that quality factors like choice of physician and continuity of care are key considerations for women's preferences for birth settings (Stevens et al, ).…”
Section: Resultsmentioning
confidence: 99%